Development and Feasibility of Lumio-Based Learning Media for Teaching Javanese Descriptive Texts in Junior High School - Febrilia, Amanda; Kurniati, Endang; Insani, Nur Hanifah (Jurnal Paedagogy, 2026)
This study aims to develop learning media for Javanese descriptive texts using Lumio by SMART and to evaluate its feasibility and trial outcomes. The research employed a Research and Development (R&D) method using the 4-D development model, which was limited to the product trial stage. The research subjects consisted of 23 seventh-grade students from a junior high school in Central Java, Indonesia, along with Javanese language teachers, subject matter experts, and media experts. Data were collected through interviews, questionnaires, and tests, and analyzed using qualitative and quantitative descriptive methods. The developed product was a Lumio by SMART-based learning medium for Javanese descriptive texts, designed according to the needs of students and teachers and containing learning materials, exercises, and evaluation activities. The expert validation results indicated that the developed media met the required feasibility criteria. Following revisions based on expert recommendations, the media was implemented in a trial phase, resulting in student learning outcomes of 82.6% in the very good category and 17.4% in the good category. Therefore, the Lumio by SMART-based learning media is feasible as an alternative digital learning medium for teaching Javanese descriptive texts to seventh-grade students at MTs NU Mawaqi’ul Ulum Kudus.